The Influence of Career Development and Compensation on Employee Performance at Bank BRI Bandar Lampung Regional Office - Dwiyanti, Septi; Puji, Kemala (Jurnal Ilmiah Sumber Daya Manusia, 2025)
The purpose of this study is to determine compensation and career development on the performance of Bank employees.BRI Regional Office of Bandar Lampung. The population in this study were employees at Bank BRI Kanwil Bandar Lampung. The sampling technique usedpurposivesamplingand obtained a sample of 50 respondents. The variables of this study use two variables, namely dependent and independent variables. For the dependent variable (y) this study is employee performance. For the independent variables (x) include Compensation (x1), and career development (x2). Quantitative data analysis methods, using several linear regression analysis models by processing data using the SPSS 21 program.Career Development partially has a positive and insignificant effect on the Performance of BRI Kanwil Bandar Lampung Employees with a t-test value of 0.371 with a significance level of 0.712. Compensation partially has a positive and significant effect on the Performance of BRI Kanwil Bandar Lampung Employees with a t-test result of 3.365 with a significance level of 0.002.As well asCareer Development and Compensation simultaneously have a positive and significant effect on the Performance of BRI Kanwil Bandar Lampung Employees with the results of the F test with ni obtained of 11,704 with a significance level of 0.000.